Generating climate change scenarios at high resolution for impact studies and adaptation: Focus on developing countries - Jones, Peter G. (2005)
This paper shows that, with existing techniques and approaches, climatic change scenarios at high resolution can be generated in developing countries despite the many remaining gaps and challenges. Firstly, current techniques and approaches for bioclimatic scenario generation are described. Then, the strengths and weaknesses of climate data, models and techniques, are discussed. The gaps and opportunities in addressing climate change are also discussed. Implications for climate change adaptation are emphasized. Finally, recommendations for addressing scientific and technological, institutional, and socioeconomic and political issues are given.